m6A reader proteins: the executive factors in modulating viral replication and host immune response - Yang, Decheng; Zhao, Guangze; Zhang, Huifang Mary (Frontiers in Cellular and Infection Microbiology, 2023)
N6-Methyladenosine (m6A) modification is the most abundant covalent modification of RNA. It is a reversible and dynamic process induced by various cellular stresses including viral infection. Many m6A methylations have been discovered, including on the genome of RNA viruses and on RNA transcripts of DNA viruses, and these methylations play a positive or negative role on the viral life cycle depending on the viral species. The m6A machinery, including the writer, eraser, and reader proteins, achieves its gene regulatory role by functioning in an orchestrated manner. Notably, data suggest that the biological effects of m6A on target mRNAs predominantly depend on the recognition and binding of different m6A readers. These readers include, but are not limited to, the YT521-B homology (YTH) domain family, heterogeneous nuclear ribonucleoproteins (HNRNPs), insulin-like growth factor 2 mRNA-binding proteins (IGF2BPs), and many others discovered recently. Indeed, m6A readers have been recognized not only as regulators of RNA metabolism but also as participants in a variety of biological processes, although some of these reported roles are still controversial. Here, we will summarize the recent advances in the discovery, classification, and functional characterization of m6A reader proteins, particularly focusing on their roles and mechanisms of action in RNA metabolism, gene expression, and viral replication. In addition, we also briefly discuss the m6A-associated host immune responses in viral infection.